Corrigendum: On the complexity of finding first-order critical points in constrained nonlinear optimization - Cartis, C; Gould, N; Toint, P (Springer, 2016)
In a recent paper (Cartis et al. in Math Prog A 144(2):93–106, 2014), the evaluation complexity of an algorithm to find an approximate first-order critical point for the general smooth constrained optimization problem was examined. Unfortunately, the proof of Lemma 3.5 in that paper uses a result from an earlier paper in an incorrect way, and indeed the result of the lemma is false. The purpose of this corrigendum is to provide a modification of the previous analysis that allows us to restore the complexity bound for a different, scaled measure of first-order criticality.